A rare case of primary cardiac lymphoma. (4th November 2015) - Khan-Kheil, Ayisha Mehtab; Mustafa, Hanif Muhammad; Anand, Dhakshinamurthy Vijay; Banerjee, Prithwish
Abstract : A 71-year-old man presented with shortness of breath and tachycardia along with systemic symptoms of weight loss and lethargy. A pulmonary embolus was the initial suspected diagnosis but through extensive investigations a rarer cause of his symptoms was identified. This case demonstrates the importance of cardiac imaging in the assessment and non-invasive tissue characterisation of a suspected cardiac tumour; in our case, this was subsequently confirmed by careful histological/immunocytochemical evaluation of the pericardial effusion as a primary cardiac B-cell non-Hodgkin's lymphoma, thus enabling appropriate management leading to an excellent clinical outcome.